SIFAT FISIK TANAH MINERAL DAN GAMBUT DI AREAL PERKEBUNAN KELAPA SAWIT DI KECAMATAN PETASIA TIMUR KABUPATEN MOROWALI UTARA - Amrin, Amrin; Ramlan, H.; Rajamuddin, Ulfiyah A. (AGROTEKBIS, 2017)
This study aims to determine the physical properties of mineral soil and peat soil in the area of oil palm plantations. This study used survey method directly at the test site and proceed it with sampling for material analyzes in laboratories. Soil analyzes carried out in laboratories of Soil Science, Faculty of Agriculture, University of Tadulako. Research conducted on 1st October to 15th January 2016. The determination of soil sampling locations for material analysis in laboratory determined intentionally (purposive sampling) at 2 units land. Soil sampling conducted in block 3 and block 9 for mineral soil. For peat soil contained in block 20 and block 24. All four blocks have the physical properties vary, bulk density is very low to moderate, permeability fast to quick fast, porosity good to porous, aggregate less steady to no steady.Â  This is because the soil was so rooted therefore affect during sampling process.Â Keywords : Mineral soil, Oil Palm, physical properties, peat soil.